Penyuluhan Fisioterapi Penerapan Program Fisioterapi sebagai Upaya Pencegahan Trigger Finger pada Pekerja Pabrik Rokok di Kedungkandang - Ervira Masagita; Sri Sunaringsih Ika Wardojo (Lembaga Pengembangan Kinerja Dosen, 2026)
Cigarette factory workers, particularly those in the rolling department, face a high risk of musculoskeletal disorders such as Trigger Finger (stenosing tenosynovitis) due to repetitive and static hand movements. A lack of knowledge regarding ergonomics and early prevention creates a significant risk of reduced work productivity. This community service initiative aimed to implement community-based physiotherapy education and self-exercise training to prevent Trigger Finger among cigarette factory workers in Kedungkandang. A descriptive method utilizing a Community-Based Participatory Research approach was employed. The study involved 30 female workers selected via purposive sampling. Interventions included health education and training on tendon gliding exercises and hand stretching. Evaluation was conducted using pre- and post-tests to measure knowledge levels, alongside observation sheets to assess practical exercise skills. Results indicated that the majority of respondents (73.3%) had more than five years of work experience. A significant improvement in knowledge levels was observed; prior to the education session, 53.4% of respondents fell into the